Strategi Meningkatkan Kualitas Pelayanan Melalui BSI Mobile Pada Bank Syariah Indonesia KC Medan Aksara - Siti Sofia Sari (Pusat Riset dan Inovasi Nasional, 2023)
Technological developments have resulted in a shift in people's frequency of transactions. For companies operating in the banking services sector, providing customer satisfaction is a basic thing that should not be ignored. Therefore, banks must improve service quality and have digital-based service innovations. The purpose of this research is to determine BSI Mobile services in an effort to improve service quality at BSI KC Medan Aksara. The method used in this research is a qualitative descriptive method by collecting data through the author's observations. The results of this research show that BSI Mobile is a super application owned by BSI because it not only has transaction features but also provides sharia features that can make transactions easier for customers. With BSI Mobile, customers can make transactions independently via BSI Mobile without having to go to a bank branch or ATM. Apart from that, the presence of BSI Mobile reduces customer queues at the banking hall, increases the number of transactions via BSI e-channels and makes service quality effective and efficient.